Protein-DNA interactions upstream from the human A gamma globin gene. - O'Neill, D (1990)
We have used DNAase I footprinting and the gel mobility shift assay to study proteins which bind to promoter elements located between -140 and -382 upstream of the human A gamma globin gene. Footprints are found with both erythroid and nonerythroid nuclear extracts at three sites: from -294 to -264, -242 to -227, and -189 to -172 from the transcription initiation site. An erythroid-specific footprint is identified from -194 to -189. We demonstrate that two known transcription factors, the ubiquitous octamer-binding protein OTF-1 and the erythroid regulatory factor NFE-1, bind to the -194 to -172 region and that their footprints overlap. Binding of OTF-1 to this region is reduced by a mutation at -175 associated with a form of non-deletion hereditary persistence of fetal hemoglobin. We conclude that OTF-1 may compete with NFE-1 for the -175 binding site, possibly functioning as a repressor of gamma globin transcription.